2016
DOI: 10.1111/eff.12307
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of changes in stable isotope ratios in the epidermal mucus and muscle tissue of slow‐growing adult catfish

Abstract: Although stable isotope analysis is a powerful tool for determining diet, migration patterns and the structure of food webs in aquatic systems, the slow response of isotopic ratios in the widely used muscle tissue often hampers this approach, particularly in slow-growing or adult fishes. We conducted a diet-switch experiment to compare the changes in the stable carbon isotope ratio (δ 13 C values) in the epidermal mucus and muscle tissue of five-year-old catfish (Silurus asotus). The isotope ratios in noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
(105 reference statements)
4
11
0
Order By: Relevance
“…These generally lower turnover rates of mucus compared with muscle were consistent with findings from the small number of other studies that have compared the turnover rates of mucus versus muscle for other fish species (e.g. Maruyama et al, 2015Maruyama et al, , 2017Shigeta et al, 2017). In our experiment, the turnover rates of d 15 N were also always greater than the rates measured for d 13 C, irrespective of diet and tissue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These generally lower turnover rates of mucus compared with muscle were consistent with findings from the small number of other studies that have compared the turnover rates of mucus versus muscle for other fish species (e.g. Maruyama et al, 2015Maruyama et al, , 2017Shigeta et al, 2017). In our experiment, the turnover rates of d 15 N were also always greater than the rates measured for d 13 C, irrespective of diet and tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Tissues are considered at equilibrium with their diet after four to five half-lives (Hobson & Clark, 1992;Busst & Britton, 2018). As different tissues tend to have different turnover rates, they can potentially be used in combination to understand changes in consumer diet across different timescales (Phillips & Eldridge, 2006;Maruyama et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is explained by the relative abundance of 13 C‐depleted lipids in different tissues, with muscle generally containing more lipids than fin or scale (Pinnegar & Polunin, ). Mucus primarily consists of glycoproteins, therefore depleted 13 C is expected and, indeed, was evident here and elsewhere (Maruyama et al, ; Nolan & Britton, ; Shigeta et al, ). Across studies, δ 15 N isotopic relationships between muscle and surrogate tissues are more varied (Hanisch et al, ).…”
supporting
confidence: 68%
“…The epidermal mucus was collected by scraping the dorsal surface of each fish with a cover slip, with the sample then cleaned with forceps as per Maruyama et al (2015) and transferred to a sample tube. This method was used in preference to the filtration method of Church et al (2009), as it was demonstrated to result in reduced error (Maruyama et al, 2017). Scales were collected from the body area between the dorsal fin and the lateral line.…”
Section: Stable Isotope Analysismentioning
confidence: 99%